Eksistensi Penggunaan Bahasa Indonesia pada Masyarakat Marginal di Demak - Rustiani, Ida; Suciati, Sri; Ripai, Ahmad (STKIP Singkawang, 2024)
Language is a connecting tool for humans in everyday life. In this world, of course, there are many languages, one of which is Indonesian. Indonesian aims to unite and make it easier to communicate between regional ethnic groups, because Indonesia has many different languages. The aim of this research was to describe, analyze and research the existence of Indonesian language use among marginalized communities in Demak. This research is qualitative with a descriptive approach. Data collection techniques through observation, distribution of questionnaires, interviews and documentation. Data analysis is carried out by presenting data in the form of tables and drawing conclusions. Based on the research results, it was found that marginalized communities in Demak only use Indonesian during formal activities or events. People in Demak tend to use regional languages or Javanese in their daily lives, this is because they feel more comfortable and proficient when communicating. Factors that influence the language use of marginalized communities in Demak, namely work factors and environmental factors.